2016
DOI: 10.5152/tud.2016.39114
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of biofeedback therapy in children with monosymptomatic enuresis resistant to desmopressin treatment

Abstract: Objective: To investigate the effect of biofeedback therapy on children with desmopressin-resistant primary monosymptomatic enuresis (MsE). Material and methods:The study comprised both retrospective and prospective sections. A total of 262 medical files of patients who were diagnosed as enuresis between November 2012 and January 2015 were retrospectively screened. Patients with neuropathic bladder, daytime voiding problems, anatomical pathology and enuresis-related diseases were excluded from the study. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Since enuresis is a disorder characterized by a deep impact on psychological, behavioral and social functioning of the child, it can benefit from a MT approach. [13][14][15][16][17][18][19][20] Our study focused on the role of MT in enuretic children undergoing pharmacological treatment or not, and its potential positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since enuresis is a disorder characterized by a deep impact on psychological, behavioral and social functioning of the child, it can benefit from a MT approach. [13][14][15][16][17][18][19][20] Our study focused on the role of MT in enuretic children undergoing pharmacological treatment or not, and its potential positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that animated BF games played an essential role in entertaining children, such that contraction and relaxation of the external sphincter more rapidly resulted in improved vesico-sphincter coordination and a significant reduction in wet night episodes. Moreover, biofeedback PFMs training modulates bladder instability by stimulating the detrusor inhibitory reflex, leading to improvement of the bladder capacity and bladder tone modulation [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to behavioral therapy, all children in the 3 groups underwent PFMs training using Kegel exercises. Children were instructed to practice 3 sets of 30 repetitions of PFMs training in the crook-lying position with 10 seconds of contraction and 10 seconds of relaxation for 30 minutes without activating the hip or abdominal muscles [10,13]. All children underwent 3 sessions per week under the therapist’s supervision and as a home routine on the other days for 3 successive months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic-floor exercise consists of tightening the pelvic muscles and holding the contraction for a period of time, followed by a resting period [11]. These changes in the electrical muscle activity are transformed into visual and audio signals [12,13]. Using surface electrodes to identify changes in muscle activity, the user is visually or audibly warned [12].…”
Section: Introductionmentioning
confidence: 99%